2020
DOI: 10.3390/su13010316
|View full text |Cite
|
Sign up to set email alerts
|

Parental Alienation-Development and Validation of a Behavioral Anchor Scale

Abstract: (1) Objective: Parental alienation phenomenon was given an increased attention during the recent years in both the clinical and the legal fields. This study aims to introduce the development of a new parental alienation questionnaire. (2) Method: Four studies were performed. In the first two studies in which five specialists participated, the questionnaire was defined, and the inter-rater reliability was verified. The next study, which included 267 participants, sought to establish the construct validity by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…One of these studies (Baker, 2020) found that professionals were accurate in their assessment of PA, particularly when PABs and PA symptoms were evident, when four factors were present in a case: previous good relationship between the alienated parent and child, lack of abuse or neglect, presence of PABS, and manifestations of PA.Thirteen studies focused on the assessment of PA in children. The measurement tools varied according to who used the tools, such as parents who identify as alienated responding to a measure of symptoms in their children (e.g., Rowlands, 2019) or clinicians using the tool (e.g., Sîrbu et al, 2020). Studies consistently found at least four attributes across all measures (e.g., Machuca, 2005), with most studies identifying eight attributes (e.g., Sîrbu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these studies (Baker, 2020) found that professionals were accurate in their assessment of PA, particularly when PABs and PA symptoms were evident, when four factors were present in a case: previous good relationship between the alienated parent and child, lack of abuse or neglect, presence of PABS, and manifestations of PA.Thirteen studies focused on the assessment of PA in children. The measurement tools varied according to who used the tools, such as parents who identify as alienated responding to a measure of symptoms in their children (e.g., Rowlands, 2019) or clinicians using the tool (e.g., Sîrbu et al, 2020). Studies consistently found at least four attributes across all measures (e.g., Machuca, 2005), with most studies identifying eight attributes (e.g., Sîrbu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The measurement tools varied according to who used the tools, such as parents who identify as alienated responding to a measure of symptoms in their children (e.g., Rowlands, 2019) or clinicians using the tool (e.g., Sîrbu et al, 2020). Studies consistently found at least four attributes across all measures (e.g., Machuca, 2005), with most studies identifying eight attributes (e.g., Sîrbu et al, 2020). The difference may be accounted for by the degree of severity of the problem or due to the participants in the sample that was investigated (e.g., professionals vs. alienated parents).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possible because animals are seen as sources of support, and when we spend time with them hormones such as dopamine, oxytocin, cortisol are released which lead to these results (Chan & Rico, 2019). It can also help bonding and improving family relationships in difficult situations (Sirbu, A., Vintila, M., Tisu, L., Stefanut, AM, Tudorel, O., Maguran, B., Toma, RA (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alienating behaviors involve one parent's intentional interference in the relationship between the child(ren) and the other parent; this interference includes behaviors meant to denigrate and reduce contact with the other parent (Sirbu et al, 2020). When the alienating parent is successful in his/her efforts and the behaviors lead to a child rejecting or not communicating with the targeted parent without any legitimate reason, the term Parental Alienation or Parental Alienation Syndrome is used (Doǧan & Aytekin, 2021).…”
Section: Characteristics Of Hcs/dmentioning
confidence: 99%